2004
DOI: 10.1088/0022-3727/37/3/014
|View full text |Cite
|
Sign up to set email alerts
|

The structure and tribological properties of gradient layers prepared by plasma-based ion implantation on 2024 Al alloy

Abstract: Using plasma-based ion implantation, two types of gradient layers have been prepared on 2024 Al alloy. One is prepared by N-implantation then C-deposition, the other adds an interlayer composed of a Ti layer and a Ti–N layer between N-implantation and C-deposition. C-deposition is carried out at various implanting voltages or C2H2/H2 ratios. The composition depth profiles of these layers were characterized by x-ray photoelectron spectroscopy. The structure, morphologies and microstructure of the C layers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 17 publications
2
19
2
Order By: Relevance
“…Cosemans et al (2003) found that by incorporation of a soft phase (MoS x ) did not lead to a decrease in hardness but significant decrease in friction coefficient compared with the results for a standard TiN coating. Liao et al (2004) studied tribological properties of gradient layers prepared by plasma‐based ion implantation on 2024 Al alloy. The evolution of the coefficient of friction can be attributed to two causes that operate in a synergistic way.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosemans et al (2003) found that by incorporation of a soft phase (MoS x ) did not lead to a decrease in hardness but significant decrease in friction coefficient compared with the results for a standard TiN coating. Liao et al (2004) studied tribological properties of gradient layers prepared by plasma‐based ion implantation on 2024 Al alloy. The evolution of the coefficient of friction can be attributed to two causes that operate in a synergistic way.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Rms measured by AFM was noted 0.54 nm (scan area; 1 × 1 μ m) by using high‐energy xenon ion beam assisted deposition of TiN film (Wang et al , 1996). Liao et al (2004) studied R a and R max of the gradient layers prepared by plasma‐based ion implantation on 2024 Al alloy by AFM.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Under some condition, a film in which the composition varies continuously from DLC (a-C:H) film to substrate could be made by PBII. Some papers reported the tribological behavior of the graded films or multi-layer films prepared by PBII on the aluminum alloy, titanium alloy or steel in ambient air or in vacuum and indicated that such films will be possible to improve the cohesion between DLC film and substrate, and therefore, improve the tribological properties [16][17][18][19][20][21][22]. For extending the area of the application, investigation of the frictional behavior of such films with different counter materials in different test environment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth, compact, adhesive and wear-resistant thin carbon films, especially dimond-like carbon (DLC) films, have been considered to be a kind of ideal lubricating and protective films for MEMS [1][2][3][4][5][6][7] owing to their excellent tribological properties and other outstanding properties [8][9][10][11] in terms of the MEMS characteristics. The quality of the carbon film depends strongly on the preparation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the carbon film depends strongly on the preparation methods. Plasma-based ion implantation (PBII) is one of the appropriate methods to prepare such carbon films because it shows unique advantages [9,12]: less than 100 • C working temperature can prevent the film from graphitizing and getting loose and rough; alternate deposition and implantation can obtain smooth, compact and adhesive carbon film; all direction-implantation can avoid the line-of-sight behaviour of normal ion beam methods and thus is fit for complicated surfaces like grooves [13]; and high implanting voltage can offer high ion energy to transform sp 2 bonds into sp 3 ones [14].…”
Section: Introductionmentioning
confidence: 99%